Prevention of Springback of High Strength Steel Sheet in L-Bending Process - Mohd Syafiq, Yusoff; Zamzuri, Hamedon (Universiti Malaysia Pahang, 2016)
Nowadays steel sheets are widely used in the industry due to the advantages of this materials in offering high strength with light weight. However due to the high tensile strength the manufacturing process need an improvement to overcome the defects occurred in the production. Therefore, a proper method is required in order to prevent the defects. In this study, a dies set with chamfers are developed to substitute the large radius that are used in current bending process. Bending process were conducted for high strength steel sheets with tensile strength of 780 MPa; to test the effectiveness of the developed die. By using this die, the chamfers enable smaller bending radius to substitute the large radius that cause the springback. It was found that the small radius produces by the chamfers are more effective in reducing the springback in L-bending of high strength steel sheets and the high press-speed will also contribute to the reducing of the springback.